2009
DOI: 10.1021/ol901570p
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed Dehydrogenative Coupling of Furans with Styrenes

Abstract: Under palladium(II)-catalyzed and oxidative conditions, the coupling of furans with styrenes leads to the formation of Heck-type products in medium to good yields. The reaction is highly regio- and stereoselective, giving trans-olefins predominantly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
39
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(42 citation statements)
references
References 34 publications
3
39
0
Order By: Relevance
“…Compound 1 and 2 a, b were synthesized as procedures reported. [16] Absorption spectra were recorded on a PerkinElmer Lambda 35 UV/Vis Spectrometer. Photoluminescent (PL) spectra were carried out on a PerkinElmer LS55 Luminescence Spectrometer.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compound 1 and 2 a, b were synthesized as procedures reported. [16] Absorption spectra were recorded on a PerkinElmer Lambda 35 UV/Vis Spectrometer. Photoluminescent (PL) spectra were carried out on a PerkinElmer LS55 Luminescence Spectrometer.…”
Section: Methodsmentioning
confidence: 99%
“…However, we propose that cocrystallized D-A systems have potential of the fluorescence recovery once force-induced phase separation occurs, which means that acceptors move away from adjacent fluorescent donors. 2,5-di(E)-distyrylfuran [16] 1 as an electron donor exhibited intensive greenish blue fluorescence both in solution and in crystal state, and planar p-conjugated structure leads to strong tendency to aggregate by p-p stacking. Meanwhile, we chose N-alkyl substituted maleimides as acceptors to quench fluorescence of donor via photo-induced electron transfer process (PET).…”
mentioning
confidence: 99%
“…We noticed an induction period during our previous study that depends on the nature of the furan, the transformation being faster with electron-rich furans. [3] We also observed that the solvent can have a decisive influence on the course of the reaction. Low-coordinating solvents led to Heck-type products, [3] whereas coordinating solvents gave difurylalkanes.…”
mentioning
confidence: 61%
“…We have recently reported an efficient method for the coupling of furans with styrenes, which allowed the use of chlorinated and fluorinated substrates. [3] However, brominated substrates were reluctant to react. These compounds would allow the synthesis of valuable products for further functionalization through other cross-coupling reactions.…”
mentioning
confidence: 99%
“…Oxidative coupling of 2-methylfuran with activated alkenes in the presence of a stoichiometric amount of palladium compounds was reported in [6]. In addition, there are published data on catalytic alkenylation of furans in the presence of catalytic systems containing palladium complexes and copper(II) salts [7], in particular palladium acetate-tert-butyl hydroperoxide-benzoquinone [8], palladium acetate-molybdovanadophosphoric acid [9], and palladium acetate-copper acetate-benzoquinone [10].…”
mentioning
confidence: 99%